The Effect of Hirudin, a Potent Antithrombin, on the Thromboplastin Generation Test - Caldwell, M. J (Thrombosis and Haemostasis, 1967)
The presence of hirudin at the time adsorbed plasma and serum were combined in TGT inhibited the formation of the prothrombin converting activity. Hirudin, a potent antithrombin, probably exerted its inhibitory effect by neutralizing any thrombin which might form. If adsorbed plasma and serum were incubated together for a period as short as 1 to 3 min before the addition of hirudin, calcium and lipid, hirudin no longer exerted the same inhibitory effect, but, in order to exert the same inhibitory effect, had to be present in higher concentration. Preincubation of factor VIII deficient plasma with serum and calcium was not effective in overcoming hirudin inhibition, but preincubation with factor IX deficient serum with adsorbed plasma and calcium was able to overcome inhibition due to hirudin equally as well as normal serum.Once again the importance of traces of thrombin in the formation of activity capable of rapidly clotting substrate plasma in TGT has been shown by using a specific thrombin inhibitor. A thrombin dependent interaction appears to take place between adsorbed plasma and serum and also between product I and phospholipid.